Story Text of Anusasana Parwa (Perspective of Hindu Religious Education) - Permana Putri, I Gusti Ayu Hyudha; Jatiyasa, I Wayan (Jayapangus Press, 2024)
The story of Anusasana Parwa is part 13 of Asta Dasa Parwa or 18 Parwa in the Mahabharata story, which tells of Yudisthira's coronation as king of Hastina replacing his uncle Drestarastra. In this Parwa it is described how the great king of the Kuru nation could reconcile himself. The awareness that grew in Yudisthira was obtained after receiving instruction from his grandfather Bhisma. This Parwa explains in detail about the rules regarding the Dharma. The general aim of this research is as a maturing process for humans through education, by adding and filling themselves through various experiences, both obtained during the learning process in class and through reading Hindu literary works. Various literary works that can be used as material for self-maturing in the world of education, especially in the Mahabharata literature in the Anusasana Parwa section. The general objective of this research is to preserve literary works as a form of language art that should be maintained, developed, and interpreted. The works can expand the treasures of Balinese culture. In addition, this research informs the existence of Hindu literary works which are very full of teachings of sraddha Bhakti, morals and ethics. This study uses a method that is relevant to the formulation of the problem and the theory used. Qualitative research methods with a descriptive approach. The results of the study show (1) The structure of the text of the Anusasana Parwa story which consists of Theme, Incident/conflict, Plot, Setting, Message which form a structure of this story. (2) In the text of the story Anusasana Parwa there are values ​​of Hindu Religious Education and Hindu Leadership values. The practice of Hindu religious education can be applied at any time or era, and under any circumstances and through any media, as is the case with the use of the Anusasana Parwa story text as a medium to understand the values ​​of Hindu religious education contained in the literary work so that it can be realized in family life, as well as the general public.